2006
DOI: 10.1080/09513590600702733
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome of clomiphene citrate/human menopausal gonadotropin/cetrorelix protocol and buserelin long protocol – a randomized study

Abstract: This study evaluates the efficacy of a stimulation protocol with clomiphene citrate (CC)/human menopausal gonadotropin (hMG)/cetrorelix and its effects on oocyte quality and endometrium. One hundred and twenty couples with male-factor infertility who were about to undergo their first intracytoplasmic sperm injection cycles were randomized into two groups. Sixty women were stimulated with the CC/hMG/cetrorelix protocol (cetrorelix group) and 60 received the buserelin long protocol (buserelin group). Fewer oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…These observations agree with previous reports, that showed that a high Gn dose is effective in getting more oocytes [8,24] and avoiding cycle cancellation [8], but does not improve IVF results [6][7][8]24]. This could be due to a negative impact of high Gn dose on endometrial quality [25] or, alternatively, to the fact that a high dose of exogenous Gn could force the recruitment of "resistant" follicles, hosting oocytes of poor quality from which poor competence embryos derive [26].…”
Section: Discussionsupporting
confidence: 91%
“…These observations agree with previous reports, that showed that a high Gn dose is effective in getting more oocytes [8,24] and avoiding cycle cancellation [8], but does not improve IVF results [6][7][8]24]. This could be due to a negative impact of high Gn dose on endometrial quality [25] or, alternatively, to the fact that a high dose of exogenous Gn could force the recruitment of "resistant" follicles, hosting oocytes of poor quality from which poor competence embryos derive [26].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that a daily dose level of 0.25 mg of cetrorelix may be too low and/or that the cetrorelix should be administered earlier to help prevent any upcoming premature LH surge among these patients. Previously, 2.5 mg of cetrorelix was administered when the leading follicle reached a size of 14 mm, and this successfully prevented premature LH surge in a COS protocol with CC and hMG during ICSI cycles (20,21). Further studies are needed to find the optimal timing and dosage for GnRH antagonist administration under the letrozole-FSH protocol.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Ingerslev et al (2001) conducted a randomised study comparing the natural cycle to the CC cycle and found a significantly higher ongoing pregnancy rate per cycle in the CC cycle than in the natural cycle (18.0% vs 3.5%, respectively). Moreover, in a study comparing 60 women who received CC ϩ hMG treatment and 60 who received the long protocol, pregnancy rates were similar between the groups (41.7% vs 40.0%, respectively) and signifi cantly fewer gonadotropin ampoules were used in the CC ϩ hMG group (Lin et al 2006). Comparing the CC and microdose GnRH agonist fl are protocols, Karimzadeh et al (2011) found similar cancellation and clinical pregnancy rates in both groups.…”
Section: Discussionmentioning
confidence: 91%